Network governance as a mechanism for responding to internet violence - Wachhaus, T. Aaron (2018)
Jones, Hesterly and Borgatti (1997) proposed a general theory of network governance (GTNG), identifying conditions under which network governance is likely to develop and detailing four social mechanisms that protect and promote resource exchange and collaborative action within a network. This article applies their theory to the emerging problem of swatting$1 (Binternet-based spoofing attacks that compel a SWAT response to a selected innocent victim. As this problem has not been addressed through traditional policy or law enforcement mechanisms, networks have emerged to respond to these attacks. The author details the parallels between these emergent networks and Jones et al.$1 (Bs theoretical framework. - Reproduced.s
Keywords: Networks; Governance